(untitled) (Global Journal of Science Frontier Research, 2017)
The two preceding papers set the stage of the new perspective for science and a book: “Infinity Contradicts Current Cosmologies”. Continuing forward here we investigate how the changes in perspective apply to numerous situations and provide value to these new perspectives. The revelations are detailed in a number of papers that provide views of what is really happening in space and cosmology. This document provides a few summaries of many of my key papers that reveal better perspectives.The many components of the whole system follow. Finally new laws of motion are provided.